Method for quick assessment of cohesive ore flowability (Research, Society and Development, 2022)
Beneficiation of iron ore with natural moisture has become increasingly relevant, either due to restrictions on wet operations, which result in disposal of tailings in dams, or due to the possibility of ready blending of various ore types. A great difficulty in these operations is handling of hydrated ores, with the presence of clay minerals, or with a higher moisture content. Effective techniques to facilitate handling emerge as the main challenge to make it possible to treat these ores under natural moisture in different plants around the world. This work aims at presenting a method for expeditious appraisal of the flowability of cohesive ore. A sample of iron ore from Mina do Pico, Brazil, was used in this study. The flowability was investigated under different conditions, using a bench scale rectangular trough with controlled slope. The following liners were studied: ASTM A-36 carbon (CDP), ultra-high molecular weight polyethylene (UHMW), Hardox, natural rubber, Arcoplate and polyurethane. UHMW resulted in the best flow efficiency and the lowest friction angle between bulk ore and the lined wall. Vibration as an ancillary agent for mechanical discharge significantly improved the flow efficiency.